Consumer’s Perception and Strategic Corporate Social Responsibility: The Case of Mobile Telecommunication Network (MTN) Company, Cameroon - Sama, Molem Christopher; Joyvice, Chofor; Buwah, Neba Noela (Journal of Asian Business Strategy, 2017)
Present day business models are fast challenging the long standing unidirectional responsibility of corporations to their stockholders. The Enlightened Self Interest concept in business ethics however contends that social performance indirectly supports the financial performance of these corporations. This assertion is based on the logic that consumers who are the ultimate drivers of the economic bottom line always perceive the social actions and sanction accordingly through loyalty and purchase preferences. Do Customers really perceive Corporate Social responsibility as intended by the corporations? This work answers this question by applying the stakeholder theory with five dimensions of social responsibility expenses on; education; sports; health; environment; art and culture in the leading Mobile Telecommunications Network (MTN) Company in Cameroon. The study adopts a time series approach and regresses quarterly expenses on five Corporate Social Responsibility (CSR) dimensions from 2001-2014 against the financial performance of the organization. The study equally applied a stratified random sample of 1000 consumers from different classes. The analyses established a highly significant relationship between corporate social responsibility expenses and the financial performance of the company, depicted by a fitness measure (adjusted R squared) of 0.986.